C-proSP-B: a possible biomarker for pulmonary diseases? - Kahn, Nicolas; Rossler, Anne-Kathrin; Hornemann, Katrin Emma; Muley, Thomas; Grünig, Ekkehard; Schmidt, Werner; Herth, Felix; Kreuter, Michael (Respiration, 2018)
Background: Detection of surfactant proteins A and D (SP-A and SP-D) in the serum of patients with pulmonary diseases is thought to reflect an injury of the alveolar epithelial barrier and as such serve as a biomarker for these diseases. However, the data for SP-B are limited. Objectives: The aim of this feasibility study was to assess whether immature SP-B pre-proteins might have value as a possible biomarker for pulmonary diseases. Methods: In serum samples from patients with different chronic lung diseases (interstitial lung diseases [ILDs], chronic obstructive pulmonary disease, asthma, lung cancer, pulmonary hypertension, inflammation, patients on ventilator support; total n = 283), C-proSP-B was measured using an electrochemiluminescence immunoassay based on mouse monoclonal anti-C-proSP-B antibodies. Levels were correlated to lung functional and clinical parameters. Results: The highest C-proSP-B levels were detected in the serum of idiopathic pulmonary fibrosis (IPF) patients. In a multivariate analysis, C-proSP-B levels were able to discriminate IPF patients from patients with all other pulmonary diseases (p < 0.0001). No significant correlations were found between C-proSP-B levels and lung function, smoking history, or disease extent. Conclusions: SP-B pre-proteins might serve as a biomarker in pulmonary diseases with alveolar or interstitial damage such as ILDs, especially in IPF. Their role in the long-term monitoring of such diseases has to be clarified further.
Gesehen am 04.11.2019